Pesticide Poisoning as a Pediatric Emergency - I. Darmansjah (Indonesian Pediatric Society, 1976)
There are branches in medicine where knowledge of the average physician is deficient, such as in pollutional problems, industrial medicine and diseases caused by agricultural chemicals. Many of these involve the toxicology of substances rarely met with in medical practice. A multidisciplinary agro-medical and industria-medical approach is essential to understand the management including precautionary and legislative measures that have to be taken. This will involve not only medical personnel but also engineers, chemists, agronomists, ecologists and many others. Poisoning with agricultural chemicals most often involve O.C. and O.P. compounds. In adults these cases have been typified by self-poisonings and through neglect of safety measures prescribed by the factory. In children poisonings almost always have been associated with accidents. Here the most important factor is also negligence of parents to keep away dangerous pesticides from the reach of children. There are quite a few potent anti dotes available in pesticide-poisoning, notably atropine for D.P.'s and carbamates, vitamin K for warfarin, and dimercaprol for arsenics. There are also chemicals like paraquat and pentachlorophenol for which no antidote is available and they present great problems in treatment.